Identification of Critical Residues in the Carboxy Terminus of the Dopamine Transporter Involved in the G Protein βγ-Induced Dopamine Efflux - Pino, José A.; Nuñez-Vivanco, Gabriel; Hidalgo, Gabriela; Reyes Parada, Miguel; Khoshbouei, Habibeh; Torres, Gonzalo E. (Frontiers in Pharmacology, 2021)
The dopamine transporter (DAT) plays a crucial role in the regulation of brain dopamine (DA) homeostasis through the re-uptake of DA. In addition to DA uptake, DAT is also able to release DA through a process referred to as DAT-mediated DA efflux. This is the mechanism by which potent and highly addictive psychostimulants, such as amphetamine (AMPH) increases extracellular DA levels in motivational and reward areas of the brain. Recently, we discovered that G protein βγ subunits (Gβγ) bind to the DAT, and that activation of Gβγ results in DAT-mediated efflux, mimicking AMPH effects. We have shown that Gβγ binds directly to a stretch of 15 residues within the intracellular carboxy terminus of DAT (residues 582 to 596). Additionally, a TAT peptide containing residues 582 to 596 of DAT was able to block the Gβγ-induced DA efflux through DAT. Here, we use computational biology, mutagenesis, biochemical, and functional assays to identify the residues within the DAT 582-596 sequence involved in the DAT-Gβγ interaction and Gβγ-induced DA efflux. Our in-silico protein-protein docking analysis predicted the importance of F587 and R588 residues in a network of interactions with residues in Gβγ. In addition, mutating F587 and R588 to alanine residues resulted in mutant DATs with attenuated DA efflux induced by Gβγ activation demonstrating the crucial role of F587 and R588 in DAT-mediated DA efflux. These results identify a potential new pharmacological target for the treatment of neuropsychiatric conditions in which DAT functionality is implicated including ADHD and drug addiction addiction.